Value relevance of goodwill accounting – how a forward-looking valuation approach guides goodwill recoverability - Ruben Just; Dirk Honold; Reinhard Meckl (Cogent Business & Management, 2023)
This study addresses the problem of value relevance and accounting for goodwill positions, as the measures used in previous studies are only suitable to a limited extent for measuring the growth potentials through M&A. For this purpose, the measure of future potential (FP) is defined as a company's expected growth from a capital market perspective, which is already priced in but has not yet been realized and separates it from the growth already realized in the income statement. The study includes 2660 acquisitions from US companies between 1998 - 2018. Goodwill (premiums) are identified as carriers of FP, and we seek to determine whether they affect long-term operating performance. Our results show that changes in FP, like goodwill, significantly negatively affect future operating performance, demonstrating the realization of growth potentials through M&A. Second, using moderation analysis, we show that the interaction between goodwill and FP predicts changes in operating performance, and the negative relationships decreased significantly when firms were able to generate more potential through the transaction. Our model is particularly suitable for acquirers who have purchased only a few FP. The controversy surrounding goodwill's value relevance and the impairment-only approach's discretionary nature is scrutinized.
Keywords: 650; future potential; goodwill; M&A; performance; premium